Pelaksanaan pembelajaran berbasis video pada mata pelajaran simulasi digital - Yesi Nurmaliza; Edy Susanto; Diah Selviani (Journal Of Dehasen Educational Review, 2021)
ABSTRACT Vocational High School (SMK) S 8 Grakarsa Bengkulu which is located on Jl. Adam Malik Km 8, Kel. Sido Mulyo, Kec. Gading Cempaka, Bengkulu City. This research is a qualitative descriptive research. The data collection technique in this study was by means of Observation, Interview, Questionnaire and Documentation, when teaching students the teacher went through (3) stages, namely the initial, core and closing stages of using learning media, knowing the concept of learning media, who used learning media, the stages of making learning media and internal and external factors that were found when video-based learning media were applied, in the implementation of learning in the room, students were seen to be active and enthusiastic in participating in learning because the teacher used video-based media by sending videos via android with an attractive display and media on when learning takes place, so that learning is interesting and good.